Brain microdialysis in neurobiology and neurochemistry - E. V. Kharitonova; O. L. Lopatina; S. A. Marchenko; Y. V. Gorina; A. B. Salmina (Фундаментальная и клиническая медицина)
Microdialysis is a versatile and popular minimally invasive technique which enables sampling, collecting, and continuous measurement of small-molecular-weight substances in the extracellular fluid of virtually any tissue. Widely established in pharmacology and neuroscience, it permits evaluation of the metabolism in any organ including brain and allows early detection of the cell stress. Concentrations of the target analytes in the dialysate are determined by the type of the analysed tissue, paracrine interactions, and technical features such as membrane type and surface area or flow rate of isotonic fluid. Cerebral (or brain) microdialysis can be used in personalised pharmacotherapy and prognostication in patients with neurological disorders. Here we discuss recent advances in brain microdialysis and focus on critical parameters defining its efficiency.